Bioelectrical Impedance Analysis: A Review - Khalsa, Er. Poonam; Manjhi, Jayanand (International Journal of Computer Sciences and Engineering, 2019)
The use of bioelectrical impedance analysis (BIA) is common in healthy people as well for patients, but lacks in different consistent mechanism and quality control measures. BIA can be used to measure the fat-free mass (FFM) and total water (TBW) in the matter without considerable fluid and electrolyte abnormalities in the case when appropriate population, age or pathologically specific BIA equations and established procedures are employed. The utilization of basic BIA measurements without relying on the use of regression prediction models and assumptions of the chemical composition of the fat-free body provides a new option for the actual assessment and clinical assessment of nutritional position and prognosis in hospitalized and elderly people. It may help improve patient care and clinical outcomes. Therefore by considering all these points, a survey is provided in this paper. The general description of BIA, types and their application used to determine FFM is demonstrated.